Ground Movements due to Shallow Tunnels in Soft Ground. II: analytical interpretation and prediction - Pinto, Federico (2013)
This paper considers the practical application of analytical solutions for estimating ground movements caused by shallow tunneling in soft ground using closed-form expressions presented in a companion paper based on linearly elastic and average-dilation models of soil behavior. The analytical solutions express two-dimensional distributions of ground deformations as functions of three parameters: the uniform convergence and relative ovalization of a circular tunnel cavity, and either the Poisson’s ratio or the average dilation angle for elastic and plastic behavior, respectively. This paper shows that the analytical predictions can achieve very good representations of the distribution of far field deformations through a series of case studies in clays and sands. In some cases, the input parameters can be interpreted from a simple calibration to three independent measurements of ground displacements comprising surface settlements above the tunnel centerline and at a reference offset, and the lateral displacement at the spring line elevation, recorded by an inclinometer at an offset of one tunnel diameter from the centerline. However, it is generally more reliable to use a least-squares fitting method to obtain the model input parameters, using all available extensometer and inclinometer data.